PROJECTION OF CHILDREN SALVATION IN NGAYUN BUDAK TRADITION IN CICINDE VILLAGE, KARAWANG, WEST JAVA, INDONESIA - Ridwan, Iwan; Widiastuti, Aries; Utami, Arista Mega; Wulandari, Rizki Ayu; Anggraeni, Suci (PEOPLE: International Journal of Social Sciences, 2016)
In this modern era, children violent cases have been currently found everywhere. It threats the harmonization of children’s life in the future. In this case, Children are the hope of the future as well as the well-young generation being prepared. So, this is cumpolsary for family members to pay more attention on their children. In Cicinde Village, Karawang, West Java, Indonesia, the term ngayunbudak tradition aims tomediatechildren who were born to obtain salvation earlier. As part of Sundanese tradition, it has some rituals such as showering the baby, serving the dish, praying, and swinging the baby. Those rituals reflect the view of a society Who are still keeping the harmonization in life.Reflected from those things, this research will reveal the problem: (1) The type and the function of ngayunbudak tradition in Cicinde Village society, Karawang, West Java, Indonesia; (2) projection of children salvation which reflects in ngayunbudak tradition in Cicinde Village society, Karawang, West Java, Indonesia. To answer those problems, this research uses qualitative ethnographic method with oral literature as a basic of the research. The technique that used is recorded and written technique. The result of this research shows that ngayunbudak tradition has a function as an education media, culture endorsement, and social control instrument in society. Nevertheless, this research reflects the life’s harmonization between human and God, and among human being.